Answer: [tex]h=\frac{-g}{g-2}[/tex]
Step-by-step explanation:
Let's solve for h.
[tex]3h+g=5h-hg[/tex]
Step 1: Add [tex]gh[/tex] to both sides.
[tex]g+3h+gh=-gh+5h+gh[/tex]
[tex]gh+g+3h=5h[/tex]
Step 2: Add [tex]-5h[/tex] to both sides.
[tex]gh+g+3h+-5h=5h+-5h[/tex]
[tex]gh+g-2h=0[/tex]
Step 3: Add [tex]-g[/tex] to both sides.
[tex]gh+g-2h+-g=0+-g[/tex]
[tex]gh-2h=-g[/tex]
Step 4: Factor out the variable [tex]h[/tex].
[tex]h(g-2)=-g[/tex]
Step 5: Divide both sides by [tex]g-2[/tex].
[tex]\frac{h(g-2)}{g-2} =\frac{-g}{g-2}[/tex]
[tex]h=\frac{-g}{g-2}[/tex]
Answer:
[tex]h=\frac{-g}{g-2}[/tex]